Autoimmunity to Tropomyosin-Specific Peptides Induced by Mycobacterium leprae in Leprosy Patients: Identification of Mimicking Proteins - Singh, Itu; Yadav, Asha Ram; Mohanty, Keshar Kunja; Katoch, Kiran; Sharma, Prashant; Pathak, Vinay Kumar; Bisht, Deepa; Gupta, Umesh D.; Sengupta, Utpal (Frontiers in Immunology, 2018)
Background: It has been shown earlier that there is a rise in the levels of autoantibodies and T cell response to cytoskeletal proteins in leprosy. Our group recently demonstrated a rise in both T and B cell responses to keratin and myelin basic protein in all types of leprosy patients and their associations in type 1 reaction group of leprosy. Objectives: In this study, we investigated the association of levels of autoantibodies and lymphoproliferation against myosin in leprosy patients across the spectrum and tried to find out the mimicking proteins or epitopes between host protein and protein/s of M. leprae. Methodology: One hundred and sixty-nine leprosy patients and 55 healthy controls were enrolled in the present study. Levels of anti-myosin antibodies and T-cell responses against myosin were measured by ELISA and lympho-proliferation assay respectively. Using 2D gel electrophoresis, western blot and MALDI-TOF/TOF antibody reactive spots were identified. Three-dimensional structure of mimicking proteins was modelled by online server. B-cell epitopes of the proteins were predicted by BCPREDS server 1.0 followed by identification of mimicking epitopes. Mice of inbred BALB/c strain were hyperimmunized with M. leprae soluble antigen (MLSA) and splenocytes, lymph node cells of these animals were adoptively transferred to naïve mice. Results: Highest level of anti-myosin antibodies were noted in sera of type 1 reaction leprosy patients. We observed significantly higher levels of lymphoproliferative response (P<0.05) with myosin in all types of leprosy patients compared to healthy controls. Further, hyperimmunization of inbred BALB/c strain of female mice and rabbit with MLSA revealed that both hyperimmunized rabbit and mice evoked heightened levels of antibodies against myosin and this autoimmune response could be adoptively transferred from hyperimmunized to naïve mice mice. Tropomyosin was found to be mimicking with ATP-dependent Clp protease ATP binding subunit of M. leprae. We found 4 mimicking epitopes between these sequences. Conclusion: These data suggest that these mimicking proteins tropomyosin and ATP-dependent Clp protease ATP binding subunit of M. leprae or more precisely mimicking epitopes (4 B cell epitopes) might be responsible for extensive tissue damage during type 1 reaction.